1976
DOI: 10.1152/jappl.1976.40.5.779
|View full text |Cite
|
Sign up to set email alerts
|

Acclimization in a hot, humid environment: cardiovascular adjustments

Abstract: Four trained young men worked for 4 h/day at 40-50% of their maximum aerobic capacity first for 3 days at 25 degrees C db, 18 degrees C wb, and then for 10 consecutive days at 45 degrees C db, 32 degrees C wb. This portion of the study was mainly concerned with central circulatory changes during acclimatization. The central circulatory adaptation to work in heat could be divided into four distinct phases: phase I (day 1) was characterized by a progressive fall in stroke volume (SV) during heat exposure but ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
59
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 0 publications
4
59
0
Order By: Relevance
“…During the prolonged treadmill work requiring 30 It/ o VOzmax in the warm humid and hot dry environ-ments, as compared to similar performance in the thermoneutral environment, our subjects exhibited the typical signs of unacclimated persons when initially exposed to work in a hot environment (2,5,15,34), ie, elevated heart rate and rectal temperature and reduced physical performance, as evidenced by the 41 070 rate of premature test interruptions. Only three subjects were able to achieve a circulatory and thermal steady state in both of the hot environments.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…During the prolonged treadmill work requiring 30 It/ o VOzmax in the warm humid and hot dry environ-ments, as compared to similar performance in the thermoneutral environment, our subjects exhibited the typical signs of unacclimated persons when initially exposed to work in a hot environment (2,5,15,34), ie, elevated heart rate and rectal temperature and reduced physical performance, as evidenced by the 41 070 rate of premature test interruptions. Only three subjects were able to achieve a circulatory and thermal steady state in both of the hot environments.…”
Section: Discussionmentioning
confidence: 76%
“…When people work for the first tim e in a hot enviro nment, their work performance is often reduced, their heart rate and internal body temperatures may increase greatly, and they are prone to heat disorders such as heat syncope and heat exhaustion (2,15,34). Depending on the severity of the environment and work load, man can adjust to a certain extent to heat stress by increased sweating and skin blood flow and thus atta in a physiological stead y state.…”
mentioning
confidence: 99%
“…This suggests that, in terms of cardiovascular adjustment, the subjects were not fully acclimated although they were from tropical areas. According to Wyndham et al (1976) their results indicated that the causes of the changes in HR during acclimatization are complex. HR is significantly correlated with both SV and T re suggesting that both an increase in SV and a fall in T re are independently associated with the decrease in HR.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear, however, whether this transient hemodilution during exercise-heat exposure following acclimatization is large enough to compensate for the displacement of blood volume into the cutaneous veins and thus provide an explanation for the reduced HR component. The proposition that a reduced HR and increased SV is the result of expansion in plasma volume during the early stages of exercise-HA has been challenged by Wyndham et al (1976). They observed that SV increases as plasma volume increased during the first six days of a ten-day acclimatization study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that exercise heat acclimation induces a significant reduction in HR, and core and skin temperatures during exercise, as well as a significant increase in SR (Gisolfi and Cohen 1979;Eichna et al 1950;Mitchell et al 1976;Wyndham et al 1976). As we did not observe a significant increase in whole-body SR throughout exercise heat acclimation, or an increase in local SR during passive heating, it is likely that the magnitude of the adaptation induced by heat acclimation was mild in the present study.…”
Section: Discussionmentioning
confidence: 99%